Case Report: Staged treatment of ankle deformity and first metatarsal deficiency after motorcycle spoke injury with Taylor external frame combined with fibular head grafting - Zhang, Le; Yan, Yuxin; Ren, Pengyu; Hou, Yong; Liu, Dan; Fan, Caiwen; Cheng, Kehuan; Zhang, Jun; Shi, Liangliang (Frontiers in Surgery, 2024)
The treatment of the sequelae of severe foot injuries caused by motorcycle spoke injury, especially in pediatric patients, allows for new options and surgical protocols. The tarsometatarsal joint and the first metatarsal were reconstructed by precise preoperative design using the TSF space external fixation technique in one stage to correct the foot deformity and restore the volume and length, and free grafting of the fibular head with epiphysis in the second stage. This method is the first of its kind reported. The patient’s foot deformity was corrected, walking, walking up and down stairs, and running functions were achieved, and the bone quality could grow with age. The combination of TSF six-axis spatial external fixation technique and microscopic technique can maximize the patient’s appearance and function and is worth promoting.